2006
DOI: 10.1007/s11134-006-0065-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a simple Markovian re-entrant line with infinite supply of work under the LBFS policy

Abstract: We consider a two machine 3 step re-entrant line, with an infinite supply of work. The service discipline is last buffer first served. Processing times are independent exponentially distributed. We analyze this system, obtaining steady state behavior and sample path properties.Keywords: Queueing, manufacturing, priority scheduling, Markovian multiclass queueing networks, last buffer first served discipline, infinite virtual buffers, steady state distributions, sample path properties, GI/M/1 queue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…In summary: For this example, each queue undergoes fluctuations in service rate around the average service rate of ν, where for alternating periods of expected duration 2T (2,2) , the service rates alternate between ν 1+r 1+2r and ν 1+3r 1+2r .…”
Section: Examplementioning
confidence: 96%
See 1 more Smart Citation
“…In summary: For this example, each queue undergoes fluctuations in service rate around the average service rate of ν, where for alternating periods of expected duration 2T (2,2) , the service rates alternate between ν 1+r 1+2r and ν 1+3r 1+2r .…”
Section: Examplementioning
confidence: 96%
“…We split the time spent in the state (2, 2) equally between the two strips. Hence the network spends an expected time 2T (2,2) = (1+r)(1+2r) μ (1−r) in each strip before moving to the other strip. Consider the horizontal strip.…”
Section: Examplementioning
confidence: 99%
“…To illustrate MaxFTP, we describe its implementation for a simple re-entrant line with 2 servers and 3 classes (this network has been recently studied in Adan and Weiss (2006)). We demonstrate the effectiveness of our results by means of simulations in which the asymptotic attributes of MaxFTP are empirically tested (Section 6).…”
Section: Introductionmentioning
confidence: 99%
“…Example 2 is a simple reentrant line. This example resembles the continuous-time reentrant line in [1]. Example 3 is the acquisition queue presented in Section II.…”
Section: Description As a Linear System With Noisementioning
confidence: 99%
“…In [1] (see also [20]) the authors have shown that a continuous-time reentrant line is stable when using the Last Buffer First Serve (LBFS) control that prioritizes step 3 over step 1, and a non-idling policy in server 2. This policy ensures that server 1 is maximally utilized.…”
Section: Example 2: Simple Reentrant Linementioning
confidence: 99%